C++ cheng xu she ji yu yan Di 4 bu fen,: Biao zhun ku : yuan shu di 4 ban / = C++ programming language - Stroustrup, Bjarne (Pearson, 2021)
Detailed summary in vernacular field,
Keywords: C++ (Computer program language); C++ (Langage de programmation)